Prediction of ammonia concentration in water based on microwave spectroscopy - S. K. Yee; S. C. J. Lim; Z. H. Liew; M. Z. N. Shaylinda; N. T. J. Ong (Bulletin of Electrical Engineering and Informatics, 2019)
Ammonia is a common pollutant in water as the result of runoff in agricultural areas where it is applied as fertilizer. It must be monitored regulary for safety purpose. The current testing technique does not allow on-site measurement as the equipment are bulky, the measurement process is time-consuming and tedious with additional mixing reagents. In this study, the presence of ammonia in distilled water is estimated from open-ended coaxial probe in the range of 200 MHz to 14000 MHz. Experimental results were obtained from two set of samples with seven different ammonia concentration each. The measurements are repeated thrice hence producing forty-two data sets with 550 points. Both curve fitting and multiple regression analysis were considered to perform valid ammonia concentration projection. Validation based on 5-fold and 10-fold cross validation suggested the feasibility of the technique as it presents root mean square error (RMSE) which is less than 0.02 in the ammonia prediction. Detection method based on open-ended probe would be convenient, simple and accurate method for in-situ determination of ammonia concentration.